Immunomodulatory Effectiveness of Aqueous Obat Pahit Extract of Lingga Malay Ethnic on White Rats (Rattus novergicus) - Fitmawati Fitmawati; Rodesia Mustika Roza; Nery Sofiyanti; Isnaini Isnaini; Febrian Lailatul Fitri; Desi Paramita; Awal Prichatin Kusumo Dewi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Obat pahit has been generally known and believed by Lingga Malay society as anti-aging agent. However, the study of Obat pahit is not scientifically proven. This research was aimed to prove immunomodulatory ability of Obat pahit potion from Lingga, Riau Archipelago. This study used white rats as an animal modelling, and Staphylococcus aureus as bacteria tester. The rats had been treated with aqueous Obat pahit extract from three TMPs on dose scales of 0.09, 0.18 and 0.27 mL/200g of body weight through oral administration for 7 days. Furthermore, on the 8th days, the experiment animals were injected by the preparation of bacteria tester through intraperitoneal administration in the amount of 0.5 mL/200 gram of body weigth and subsequently incubated for 1 hour after the injection. There were 2 observed parameters on this study, i.e efectivity and capacity of phagocytosis by leukocytes. The observation of leukocytes-phagocytocis activity was carried out by making a smear preparat samples of peritoneum fluid from rats. After the observation under microscope on a magnification of 100 times. The result was obtained the Obat pahit from Kalan PMT swere more effective on dose 2, while from SP4 and Linau TMPs were much more effective on dose 1. It is therefore, using these data of the results, the advanced doses scale of this Obat pahit would not be necessary. Obat pahit potion from Malay Lingga Malay Ethnic could become raw materials of immunomodulatory herbal medicine based on traditional knowledge. It also potentially as a standardized herbal.